Aktivitas Motorik Halus Anak di TK Aisyiyah Aek Kanopan - Widya Firdausi Lasty; Berlianti Panjaitan (Fakultas Syariah IAIN Laa Roiba Bogor, 2020)
The focus of this research is how the ability of children's fine motor activities and how they are implemented as well as the results obtained after the activity by the teacher during the learning and teaching process at Aisyiyah Aek Kanopan Kindergarten. Fine motor activity is a body movement that involves small muscles, especially those involving the muscles of the hands and fingers. Usually fine motor activities of high accuracy, require work and coordination between the eyes and small muscles. This study uses the observation method, namely data collection by direct observation of the object of research, namely communicating directly with sources, documentation, namely collecting data from written sources or documents. Data analysis used to analyze data obtained from observation sheets or observations and interviews. From the results of the study, it was found that in increasing the ability of fine motor activities of children in Aisyiyah Aek Kanopan Kindergarten, it was supported by the role of the teacher and the stages of implementing fine motor activities which were very supportive in improving children's fine motor skills. There are four fine motor activities carried out, namely (1) Drawing; (2) Playing Dough; (3) Collage; (4) Splashing. The results or outputs achieved from fine motor activities are increasing interest and fine motor skills in children. Students are increasingly fond and happy in doing fine motor activities besides that, students have started to be independent and more focused when doing fine motor activities. Keywords: Children's activities, motor, children’s fine